2020
DOI: 10.3390/cells9020375
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Regulates Collagen Type I Expression in Myoblasts and Myotubes via Transient Ctgf and Fgf-2 Expression

Abstract: Transforming Growth Factor β (TGF-β) is involved in fibrosis as well as the regulation of muscle mass, and contributes to the progressive pathology of muscle wasting disorders. However, little is known regarding the time-dependent signalling of TGF-β in myoblasts and myotubes, as well as how TGF-β affects collagen type I expression and the phenotypes of these cells. Here, we assessed effects of TGF-β on gene expression in C2C12 myoblasts and myotubes after 1, 3, 9, 24 and 48 h treatment. In myoblasts, various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…FGF12 belongs to the FGF family [ 49 ], similar to other FGF members [ 50 ], FGF12 function as a secretory antagonist of signaling molecules such as Wnt, TGF [ 51 , 52 ]. FGF signaling was the epithelial signal that regulates the dermal condensate formation and subsequently affects hair follicle morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…FGF12 belongs to the FGF family [ 49 ], similar to other FGF members [ 50 ], FGF12 function as a secretory antagonist of signaling molecules such as Wnt, TGF [ 51 , 52 ]. FGF signaling was the epithelial signal that regulates the dermal condensate formation and subsequently affects hair follicle morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor β (TGF-β) is elevated in muscle injury and also in pathological conditions such as DMD. TGF-β is a well-known regulator of muscle fiber size but also causes elevated collagen type I expression from both myoblasts and differentiated myotubes in cell culture (Hillege et al, 2020). Myogenic progenitor cells arising from satellite cells in growing or repairing muscle form part of the regulation of synthesis of new collagen in the IMCT by fibroblasts.…”
Section: Changes Of Imct In Muscle Adaptationmentioning
confidence: 99%
“…18 It is reported that there is a positive regulatory relationship between COL1A1 and TGF-β signaling. [19][20][21] However, there is no similar finding in GC.…”
Section: Introductionmentioning
confidence: 95%